EES based Software Development of Thermal Performance for Teluk Sirih Steam Power Plant - Hidayatullah, Muhammad
Sustainable optimum level of thermal performance in a coal-fired steam power plant (CFPP) can be achieved by a continuous program of evaluation of thermal performance data. Process of assessment and evaluation needs tool that can help it so that process takes less time and more accurate. Analysis program as a tool for evaluating thermal performance data will be designed in this research. The program focuses on evaluating thermal performance Teluk Sirih CFPP. The program will be formulated using EES program. All of thermal performance parameter analysis steps will be made in accordance to ASME PTC 4.1 which discusses about steam generator testing procedure and AMSE PTC 6 which discusses about steam generator testing procedure. These following are all activities that occurs during this research, collecting Performance Guarantee data, calculating thermal performanceusing formulated software, validating the thermal performance calculation result and comparing the thermal performance calculation result with performance guarantee. Thermal performance parameters that are concerned in this research are steam generator LHV basis, GTHR, GPHR LHV basis, and NPHR LHV basis. The calculation result for steam generator efficiency LHV basis, GTHR, GPHR LHV basis, and NPHR LHV basis are 90,62%, 2137 kcal/kWh, 2358 kcal/kWh, and 2682 kcal/kWh. These calculation shows that designed software works dan calculates well and Teluk Sirih CFPP has a good thermal performance.